Current controversies in prenatal diagnosis 2: The 59 genes ACMG recommends reporting as secondary findings when sequencing postnatally should be reported when detected on fetal (and parental) sequencing. (17th April 2020) - Amor, David J.; Chitty, Lyn S.; Van den Veyver, Ignatia B.
Abstract: Genome sequencing is increasingly being used to aid genetic diagnosis in fetuses with structural abnormalities detected on ultrasound examination. However, with clinical exome and genome sequencing, there is potential for the recognition and reporting of incidental or secondary findings unrelated to the indication for ordering the sequencing, but of potential medical value for patient care. In the postnatal setting, the American College of Medical Genetics and Genomics (ACMG) has clear guidelines that state that when offering sequencing, secondary findings should be reported in 59 genes for which ACMG consider there is a clinical evidence that pathogenic variants may result in disease that might be prevented or treated, with the option to opt out of receiving this information. However, these guidelines specifically exclude prenatal sequencing. Here, we report the debate on whether or not pathogenic findings in these 59 genes should or should not be reported in the prenatal setting. Although more were in favour of reporting before the debate, there was no significant consensus from the audience. After the debate there was a swing toward not reporting, but a slim majority (55%) remained in favour, indicating that this is an area requiring further research and the development of evidence‐based guidelines applicable to prenatal proband and trio sequencing.